Eksistensi Kearifan Lokal di Era Globalisasi: Tantangan dan Solusi: (Analisis Historis : Dampak Negatif, Strategi, Urgensi) - Abu Haif; Susmihara (Tumanurung: Jurnal Sejarah dan Budaya, 2025)
Globalization has become an inevitable phenomenon in modern life, exerting a profound influence on various aspects of life, including local culture. On one hand, globalization offers opportunities such as broader access to information, technology, and innovation. On the other hand, it poses serious challenges to the preservation of local wisdom, which has long been the identity and cultural heritage of communities. Local wisdom reflects noble values, traditional knowledge, and cultural practices passed down through generations. However, the strong currents of global culture often result in the erosion of local values, cultural homogenization, and the decline of social solidarity. This article aims to examine the negative impacts of globalization on the existence of local wisdom while offering strategies to preserve it. Using a descriptive qualitative approach, the article highlights the importance of education, technology, community, and government policies in maintaining local values amidst modernization. The findings reveal that despite the threats globalization poses to local culture, it also offers opportunities to use globalization as a tool to strengthen cultural identity. This article underscores the urgency of local wisdom in shaping a more harmonious and sustainable civilization, including its contributions to social, economic, and environmental development. Therefore, collaborative efforts among the government, communities, and younger generations are essential to ensuring local wisdom remains relevant in the globalization era.